A New Colorimetric DPPH Radical Scavenging Activity Method: Comparison with Spectrophotometric Assay in Some Medicinal Plants Used in Moroccan Pharmacopoeia - Babili, Fatiha EL; Nigon, Clotilde; Lacaze, Li; Millé, Juliette; Masiala, Anthony; Simm, Jennifer; Lamade, Virginie M.; Haj, Amal Ait El (Pharmaceutical Fronts, 2022)
Antioxidants in medicinal plants are particularly important in protecting against reactive oxygen species (ROS)-related diseases, such as heart and blood vessel disease, nervous system degeneration, and cancer. Because our bodies are not strong enough to completely neutralize ROS, we sometimes need antioxidant supplementation from herbs. There is ample empirical evidence in traditional pharmacopoeias. The antioxidant activities of plant drugs have long been spectrophotometrically measured with 2,2-diphenyl-1-picrylhydrazyl (DPPH). In this study, a new colorimetry DPPH radical scavenging activity method (validated to ICH standards) for some medicinal plants, used in Moroccan pharmacopoeia, was reported and made a comparison with spectrophotometric assay. In the method, a solution of DPPH• is incubated in the presence of an antioxidant control (Trolox) or medicinal plant extracts in wells on a 96-well plate. After an appropriate reaction time, in the dark, the plate was scanned and images obtained were processed and analyzed by Image J software. This analysis will allow us to evaluate substance's antioxidant activity, almost in the same way as a spectrophotometric assay. The colorimetric DPPH• method exhibited a strong correlation (R2 > 0.95) with the conventional spectrophotometric DPPH• method. The colorimetric DPPH• method had excellent accuracy (103.81–105.47%), precision (1.051–10.85% RSD [relative standard deviation]), reproducibility (1.457% RSD), and robustness (1.05–1.38 F test). The developed DPPH• test was easy, fast, low cost and reliable, and can be used for high-throughput assay for screening DPP-scavenging activity in herb medicines.
Keywords: colorimetric DPPH• method; herbal drugs; antioxidant activity; screening; pharmacopoeia